BIBLIOTHERAPY IN REDUCING DEPRESSION TENDENCIES IN COLLEGE STUDENTS - Lidini Natsir; Sitti Murdiana; Haerani Nur (Universitas Islam Indonesia, 2023)
ABSTRACT: College students are particularly susceptible to depression due to the various pressures. Therefore, bibliotherapy is one of the interventions that can be utilized to alleviate this situation. This study aimed to determine the effectiveness of bibliotherapy in reducing the tendency of depression among students. The participants in this pre-experimental study with a one-group pretest-posttest design consisted of college students who experienced depression and had an interest in reading (N=7). The results of the Wilcoxon test showed a decrease in depression symptoms after students received bibliotherapy intervention. This study was expected to serve as a valuable self-help reference for students struggling with depression.